Does big data ring a bell? Analyzing the understanding of big data at local government in indonesia - Djoko Sigit Sayogo; Sri Budi Cantika Yuli (Journal of Innovation in Business and Economics, 2022)
This paper attempts to portray public managers' perceptions concerning the big data concept using the case of a local government level in Indonesia. This study conducted in-depth semi-structured interviews with sixteen (16) top-level executives at the agencies and offices of the Regency of Bojonegoro, Indonesia, to gather the data. Our findings demonstrate that most of the executives from the agencies and offices in the Regency of Bojonegoro cannot fully explain what constitutes the big data indicators. However, the majority recognized big data from the volume perspective. Although, several executives mixed up big data with the infrastructure needed to manage the data in terms of storage and preservation. As such, this confusion could presumably also manifest in their comprehension of using data for decision-making. The lack of trust in data, lack of understanding of big data, and overconfidence in personal insights have driven the decision-makers to forego data and rely on intuition and experiences in making decisions.